2014
DOI: 10.1122/1.4903498
|View full text |Cite
|
Sign up to set email alerts
|

Individual chain dynamics of a polyethylene melt undergoing steady shear flow

Abstract: Individual molecule dynamics have been shown to influence significantly the bulk rheological and microstructural properties of short-chain, unentangled, linear polyethylene liquids undergoing high strain-rate flows. The objective of this work was to extend this analysis to a linear polyethylene composed of macromolecules of a much greater length and entanglement density; i.e., a liquid consisting of C 400 H 802 molecules, with approximately ten kinks per chain at equilibrium, as calculated by the Z1 code of Kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
156
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(190 citation statements)
references
References 55 publications
(136 reference statements)
34
156
0
Order By: Relevance
“…As noted in the introduction hints of ES are observed in molecular dynamics simulations of linear polymers [Sefiddashti et al (2015)] and in slip-link simulations [Masubuchi et al (2012[Masubuchi et al ( , 2014; Andreev et al (2013)]: These methods may provide corroboration of the assumptions in the present model for branched polymers. A more detailed tube model description of branched polymer dynamics might seek to capture the nested tube structure suggested by constraint release models, and to couple the dynamics of adjacent polymer segments in a branched molecule.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As noted in the introduction hints of ES are observed in molecular dynamics simulations of linear polymers [Sefiddashti et al (2015)] and in slip-link simulations [Masubuchi et al (2012[Masubuchi et al ( , 2014; Andreev et al (2013)]: These methods may provide corroboration of the assumptions in the present model for branched polymers. A more detailed tube model description of branched polymer dynamics might seek to capture the nested tube structure suggested by constraint release models, and to couple the dynamics of adjacent polymer segments in a branched molecule.…”
Section: Discussionsupporting
confidence: 74%
“…There are also indications of ES in recent computer simulation, e.g., the work of Sefiddashti et al (2015). However, in the context of branched polymers and the pom-pom model, the effects of ES are potentially very strong: (i) The onset of branch-point withdrawal within the model provides an occasion for a sudden and rapid increase in the amount of ES.…”
Section: Introductionmentioning
confidence: 99%
“…Costanzo et al 7) proposed the tumbling motion of entangled polymers, an unexpected molecular mechanism just discovered in the nonequilibrium molecular dynamics simulations of Nafar Sefiddashti et al 9) . Inspired by the damped oscillations shown in the end-to-end vector autocorrelation function, as observed by Nafar Sefiddashti et al 9) at the steady state of fast shear flows, Costanzo et al 7) introduced a damped oscillating tumbling function into the equation for the chain stretch dynamics, while leaving unaltered the equation for the orientation dynamics.…”
Section: Introductionmentioning
confidence: 91%
“…Inspired by the damped oscillations shown in the end-to-end vector autocorrelation function, as observed by Nafar Sefiddashti et al 9) at the steady state of fast shear flows, Costanzo et al 7) introduced a damped oscillating tumbling function into the equation for the chain stretch dynamics, while leaving unaltered the equation for the orientation dynamics. Such a simplified approach, however, has been recently questioned in a second paper by Nafar Sefiddashti et al 10) , who analyzed nonequilibrium molecular dynamics simulations also under transient startup of fast shear flows, revealing undershoots.…”
Section: Introductionmentioning
confidence: 99%
“…These simulations thus revealed that inclusion of constraint release events played an important role in the emergence of the plateau region and concomitant mitigation of the drop in stress, as predicted by the DE theory. Recent atomistic simulations of unentangled [15] and mildly entangled [16] polyethylene (PE) melts showed that individual chains experience retraction and rotation cycles within oriented tubelike structures formed by highly stretched surrounding chain molecules at large strain rates. The onset of chain rotation was attributed to the flowinduced disentanglement of polymer chains that occurs at high shear rates in steady shearing flow [16].…”
Section: Introductionmentioning
confidence: 99%